The extracellular contractile injection system is enriched in environmental microbes and associates with numerous toxins - Alexander Martin Geller (Nature Portfolio, 2021)
The extracellular Contractile Injection System (eCIS) is a toxin-delivery particle that mediates interactions between bacteria and their invertebrate hosts. Here, the authors catalogue eCIS loci from 1,249 prokaryotic genomes, showing enrichment in non-pathogenic environmental microbes, and identifying eCIS-associated toxins that inhibit the growth of bacteria and/or yeast.